Differential pulse polarographic determination of clotrimazole after derivatization with Procion Red HE-3B - Pereira, F. C.; Zanoni, Maria Valnice Boldrin [UNESP]; Guaratini, CCI; Fogg, A. G. (Elsevier B.V., 2002)
Clotrimazole was shown to react at room temperature in Britton Robinson buffer pH 2 with the reactive dye Procion Red HE-3B. The product exhibited a differential pulse polarographic peak at -0.38 V, which was well separated from the peaks of the reactive dye at -0.08, -0.80 and -0.95 V, and this allowed the indirect determination of clotrimazole in the presence of excess of the reactive dye. The method has been applied satisfactorily to the determination of clotrimazole in pharmaceutical formulations, calibration graphs are rectilinear up to at least 40 mug ml(-1). The detection limit was calculated to be 2.6 mug ml(-1) (3 sigma). (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: clotrimazole; differential pulse polarography; Procion Red HE-3B dye